Headache: A burden in female life and its self-care - Muthyala Nagavamsidhar; Hari Kiran; Qadrie ZL; Suman A; Athifa B; Vijaya laxmi T (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2019)
Background: Headache is one of the deliberating disease affecting all most all population around the globe. There are classifi ed according to ICH guidelines and well explained with three hypotheses. Management includes both pharmacological and non-pharmacological treatment. In female, period between menarche and menopause is bonded with frequent headache due to hormonal fl uctuations which can be managed with couple of medications and lifestyle modifi cations. Objectives: To know the frequency and self-care of headache in young adult females and to determine the trigger factors of headache in them. Methods: In this cross-sectional study, a validated self-administered, questionnaire was used to collect data among female about 17-24 years.